The political ecology of land management in the oil palm based cropping system on the Adja plateau in Benin - YEMADJE, HANS ROLAND; CRANE, TODD; VISSOH, VINASSÉHO PIERRE; MONGBO, ROCH LAMBERT; RICHARDS, P.; KOSSOU, KODJO DANSOU; KUYPER, W. THOM (My University, 2012)
The Adja plateau (Benin) is densely populated by tenant and landowner farmers engaged in oil palm based cropping. Landowners use oil palm sap for the production of sodabi (a local spirit), and an oil palm fallow (if no crops are grown beneath the palms) to restore soil fertility. In this area, growing oil palm for its oil is uncommon. Tenants access the land under specific contracts but are not allowed to plant oil palm. They grow food crops beneath the oil palm and extend the cropping period by severely pruning the palms because their right to grow food crops terminates when the palms reach a height of 2 m. The competing claims between landowners and tenants and between oil palm and annual food crops result in conflicts over practices that either degrade or restore soil fertility. Using a political ecology perspective, we examined how two overlapping institutions shape access to and management of the land: the customary tenure system and the legal system that was introduced to regulate titling and contracting. These institutions have divergent implications for tenants and landowners, in terms of both social equity and land management practices. The implications of this institutional patchwork (bricolage) for joint learning to achieve sustainable agriculture are discussed.
Keywords: Bricolage - Customary land rights - Institutions - Oil palm fallow - Political ecology - Benin